Colombia, Brazil, Argentina and Chile: educational practice and pedagogical orientations - Ayala Zuluaga, Carlos Federico; Tadeu Iaochite, Roberto; de Souza Neto, Samuel (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This article discusses aspects of the Educational Practice in four state universities in: Colombia, Brazil, Argentina, and Chile. We also take into account the conceptual orientations in teacher training proposed by Feiman (1990) and Imbernon (2007). The research approach is qualitative and aims to understand intrinsic, regional, cultural, and political aspects of educational practice related to pedagogical orientations, through a process of fluctuating pre-analysis of information, coding and identification of categories. The final stage consisted of description, categorization, inference and interpretation of the information collected. The results show that pedagogical orientations converge in action, reflection, knowledge, the use of digital information and communication technologies, and in the development of the teaching identity. Main conclusions: the predominant pedagogical orientations in the state education are the academic and the technical, and in the universities were identified the traditional, academic, social effectiveness, hermeneutics, and process-centered.